1996
DOI: 10.1016/s0735-1097(96)00310-5
|View full text |Cite
|
Sign up to set email alerts
|

A model that predicts morbidity and mortality after coronary artery bypass graft surgery

Abstract: Analysis of preoperative patient variables can predict patients at increased risk for morbidity or mortality, or both, after bypass surgery. Increased morbidity results in higher costs. Different strategies for high and low risk patients should be used in cost reduction efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0
6

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(85 citation statements)
references
References 12 publications
5
74
0
6
Order By: Relevance
“…Another mortality predictor introduced in 1992 was the Northern New England score which was developed for isolated CABG operations and included preoperative dialysis dependency as a surrogate for high serum level of creatinine [140] . Nilsson et al [3] and Magovern et al [141] developed another risk algorithm to be applied in isolated CABG with promising results compared to a group of 18 risk models.…”
Section: Creatinine and The Outcome Prediction In Cardiac Surgerymentioning
confidence: 99%
“…Another mortality predictor introduced in 1992 was the Northern New England score which was developed for isolated CABG operations and included preoperative dialysis dependency as a surrogate for high serum level of creatinine [140] . Nilsson et al [3] and Magovern et al [141] developed another risk algorithm to be applied in isolated CABG with promising results compared to a group of 18 risk models.…”
Section: Creatinine and The Outcome Prediction In Cardiac Surgerymentioning
confidence: 99%
“…Using univariate and multivariate logistic models, Zindrou and coworkers 1 found that a low hemoglobin level was a predictor of in-hospital death after CABG. In the risk-prediction model of Magovern and associates, 2 anemia was an independent predictor for mortality or morbidity. Kulier and colleagues 3 reported that a low preoperative hemoglobin level was an independent risk factor for renal and neurological complications, whereas an increase in cardiac events was due to other factors associated with preoperative anemia, such as renal dysfunction.…”
mentioning
confidence: 91%
“…However, in the study of Weber et al, there was no association between preoperative anemia and increased surgical site infection [24]. Other studies found a non-significant relationship, or one with a smaller odds ratios [25,26]. The Kulier et al study showed a significant relationship between preoperative low Hgb and non-cardiac-but not cardiac-complications [1].…”
Section: Discussionmentioning
confidence: 92%